The miR-372-ZBTB7A Oncogenic Axis Suppresses TRAIL-R2 Associated Drug Sensitivity in Oral Carcinoma - Yeh, Li-Yin; Yang, Cheng-Chieh; Wu, Hsiao-Li; Kao, Shou-Yen; Liu, Chung-Ji; Chen, Yi-Fen; Lin, Shu-Chun; Chang, Kuo-Wei (Frontiers in Oncology, 2020)
miR-372 has been shown a potent oncogenic miRNA in the pathogenesis of oral squamous cell carcinoma (OSCC). The zinc finger and BTB domain containing 7A protein (ZBTB7A) is a transcriptional regulator that is involved in a great diversity of physiological and oncogenic regulation. However, the modulation of ZBTB7A in OSCC remains unclear. Tissue analysis identifies a reverse correlation in expression between miR-372 and ZBTB7A in OSCC tumors. When OSCC cells have stable knockdown of ZBTB7A, their oncogenic potential and drug resistance is increased. By way of contrast, such an increase is attenuated by expression of ZBTB7A. Screening and validation confirms that ZBTB7A is able to modulate expression of the death receptors TRAIL-R1, TRAIL-R2, Fas and p53 phosphorylated at serine-15. In addition, ZBTB7A transactivates TRAIL-R2, which sensitizes cells to cisplatin-induced apoptosis. The ZBTB7A-TRAIL-R2 cascade is involved in both the extrinsic and intrinsic cisplatin-induced pathways of apoptosis. Database analysis indicates that the expression level of and the copy status of ZBTB7A and TRAIL-R2 are important survival predictors for head and neck cancers. Collectively, this study indicates the importance of the miR-372-ZBTB7A-TRAIL-R2 axis in mediating OSCC pathogenesis and in controlling OSCC drug resistance. Therefore, silencing miR-372 and/or upregulating ZBTB7A would seem to be promising strategies for enhancing the sensitivity of OSCC to cisplatin and other TRAIL-base therapies.